Outcome probability versus magnitude: when waiting benefits one at the cost of the other. - Michael E Young; Tara L Webb; Jillian M Rung; Anthony W McCoy (PLoS ONE, 2014)
Using a continuous impulsivity and risk platform (CIRP) that was constructed using a video game engine, choice was assessed under conditions in which waiting produced a continuously increasing probability of an outcome with a continuously decreasing magnitude (Experiment 1) or a continuously increasing magnitude of an outcome with a continuously decreasing probability (Experiment 2). Performance in both experiments reflected a greater desire for a higher probability even though the corresponding wait times produced substantive decreases in overall performance. These tendencies are considered to principally reflect hyperbolic discounting of probability, power discounting of magnitude, and the mathematical consequences of different response rates. Behavior in the CIRP is compared and contrasted with that in the Balloon Analogue Risk Task (BART).